2013
DOI: 10.1007/s11010-013-1623-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of estrogen on prolidase-dependent regulation of HIF-1α expression in breast cancer cells

Abstract: The role of estrogen in breast cancer progression and activation of prolidase activity and HIF-1α led us to study the effect of estrogen on nuclear HIF-1α expression in breast cancer estrogen-dependent MCF-7 and estrogen-independent MDA-MB-231 cells. We have found that in MCF-7 cells (expressing α and β estrogen receptor) cultured without estrogen receptor activator (phenol red, estradiol), HIF-1α was down-regulated, compared to the cells cultured with estrogen receptor activator. This effect was not observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Additionally, HIF-1α proteosomal degradation may be the result of the expression of either von Hippel-Lindau E3 ubiquitin-ligase (9) or Sharp-1, a basic helix-loop-helix transcription factor (24) . Molecular studies by Surazynski et al might be to some extent a confirmation of our findings on the relationship between HIF-1α and ER (25) . The authors suggested that α-estrogen receptor up-regulates the activity of prolidase, which in turn contributes to an increase in HIF-1α nuclear localization.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, HIF-1α proteosomal degradation may be the result of the expression of either von Hippel-Lindau E3 ubiquitin-ligase (9) or Sharp-1, a basic helix-loop-helix transcription factor (24) . Molecular studies by Surazynski et al might be to some extent a confirmation of our findings on the relationship between HIF-1α and ER (25) . The authors suggested that α-estrogen receptor up-regulates the activity of prolidase, which in turn contributes to an increase in HIF-1α nuclear localization.…”
Section: Discussionsupporting
confidence: 90%
“…Proline, by inhibition of HIF prolyl hydroxylase activity [4] suppresses proteosomal degradation of HIF-1α and increases HIF-1α transcriptional activity [4, 7, 47]. Therefore, increase in cytoplasmic proline concentration, which mostly depends on prolidase activity, contributes to increase in HIF-1α transcriptional activity [4].…”
Section: Discussionmentioning
confidence: 99%
“…Triple-negative breast cancers (TNBCs), which are characterized by lacking expression of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor2 (HER2), comprise 15–20% of breast cancer cases and are considered the most malignant subtype, with the highest risk of metastasis ( 2 ). TNBCs more frequently disseminate to the distant organs, including brain, lung and liver, than to regional lymph nodes ( 2 , 3 ). Metastasis is regarded as the key contributor to breast cancer-associated mortality.…”
Section: Introductionmentioning
confidence: 99%